Perancangan dan pelaksanaan foto profile guru sebagai media identitas profesional di SD Charitas Batam - Randy Sitompul; Syaeful Anas Aklani; Mangapul Siahaan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This project aims to design and implement a professional teacher profile photo session at SD Charitas Batam, as part of enhancing teacher identity and the school’s image in the digital era. Based on observations and interviews with the school, it was found that most teachers did not have standardized and high-quality profile photos. Therefore, a visual concept was planned, followed by a structured photoshoot and photo editing process focused on producing professional, neat, and representative portraits. The final photos were used for administrative purposes, school websites, social media, and other official publications. The results showed that teachers now have more consistent visual identities, contributing to the branding of SD Charitas Batam as a modern and credible educational institution.